Factors and patterns of technical and technological development of enterprises' bases - Oleksandr Emelyanov; Tetiana Petrushka (Cхід)
The factors grouping, which is made for the development of technical and technological base of the company at their place of origin is developed by means of dividing the factors that arise: during the enterprise development process, design and manufacture of the elements, the process of supply of raw materials, in process of consumers, in the functioning of resource markets, in the operation of public authorities.